Poetic Commitment and the Individual Publisher: Some Reflections on the Houghton Mifflin New Poetry Series. - Pinsker, Sanford (Literary Review)
The article discusses the New Poetry Series published by the Houghton Mifflin publishing house, with particular focus given to editor Thomas Hart's willingness to publish unknown poets working in a variety of styles. Books in the series including "Hush" by David St. John, "Dangers" by Heather McHugh, and "The Ruined Motel" by Reginald Gibbons are also examined.